412 Return to work and work sustainability among japanese cancer survivors. (24th April 2018) - Endo, Motoki
Abstract : Introduction: In developed countries, the population ages with increasing cancer survival rates, the proportion of working-age cancer survivors is expected to increase. In Japan, it seems that there has been more interest in follow up for employees who returned to work after sick leave due to cancer. The aim of this study is to investigate work sustainability of cancer survivors after RTW and to make 'Evidence Book for work among cancer', 'Guidance for work among cancer survivors, stratified by cancer type', 'Card between clinics and companies, stratified by cancer type'. Methods: We collected sick leave data of 1278 cancer survivors in a registered Health Data. This is supported by a Health Labour Sciences Research Grant, Japan (Endo-Han). As for 'Evidence Book', we collected our previous studies and others. As for 'Guidance' and 'Card', we made six project team by cancer type (breast cancer, colon cancer, gastric cancer, genitals malignancies, lung cancer etc). Result: According to our previous studies, 47.1% returned to work full time within 6 months of their initial day of sick leave absence, and 62.3% by 12 months. The cumulative RTW rate varied significantly by cancer type. Of workers who returned to work after their first episode of leave after cancer, more than 50% continued to work after 5 years in large-scaled companies. There was a steep decrease in work continuance rates during the first year after RTW, with considerable differences according to cancer site. Discussion: It is very important for companies (especially small- and medium-sized companies) to establish and improve their RTW support system for employees with cancer.